Association of clinically significant weight loss with number of patient visits and months of attendance at an Australian multidisciplinary weight management clinic. Issue 3 (27th March 2022) - Chen, Juliana; Kaur, Harpreet; Jaques, Joanna; Rock, Zoe; Dean, Catherine M.; Lord, Reginald V.; Preda, Veronica
Summary: Despite the obesity epidemic, there are relatively few multidisciplinary obesity services in Australia, and only limited data on the effectiveness of these services. The aim of this study was to evaluate the effectiveness of a university hospital‐based weight management clinic—the ' Healthy Weight Clinic ' in supporting patients to achieve clinically significant weight loss (≥5% reduction in body weight), weight maintenance, and changes in body composition. A retrospective review was conducted to determine weight and associated health outcomes in patients who attended an initial consultation in the first 2 years of the clinic—between March 2017 and March 2019. Follow up was at least 1 year for all patients. Patients who underwent bariatric surgery were excluded. Of 213 total patients, 172 patients attended more than one follow‐up consultation for lifestyle modification. Mean weight change and percentage total weight change at last follow‐up was −6.2 kg (SD 7.4) and − 6.0% (SD 6.9), respectively. For every additional clinic follow‐up, there was 21.4% increased odds of achieving clinically significant weight loss, and for every additional month of follow‐up, there was 10.1% increased odds of achieving clinically significant weight loss. Twenty percent of patients (34/172) maintained ≥5% of initial body weight loss for at least 1 year. Body composition measurements were also favourable, with significant changes in percentage skeletal muscle mass of +0.8% (SD 1.5) and in percentage fat mass by −1.4% (SD 3.2). Regular support in a structured holistic multidisciplinary obesity service enables patients to achieve clinically meaningful weight loss and improved skeletal muscle mass to body fat ratio, and maintain this loss for at least 1 year. Improved weight loss was associated with more patient visits and longer duration of attendance at the clinic.